Low-carbon stabilization of expansive soils using cement kiln dust and calcium carbide slag: mechanisms and performance - Yan, Qiangzhen; Peng, Bo; Li, Wenwei; Wang, Baotian; Zuo, Jinyu; Lv, Guangdong; Wang, Tongzhang (Frontiers in Earth Science, 2025)
In response to the environmental challenges posed by conventional expansive soil stabilization methods, this study investigates the low-carbon potential of industrial by-products—cement kiln dust (CKD) and calcium carbide slag (CCS)—as sustainable stabilizers. A comprehensive series of laboratory tests, including compaction tests, free swelling rate measurements, unconfined compressive strength (UCS) evaluations, and scanning electron microscopy (SEM) analyses, were conducted on expansive soil samples treated with varying dosages in both single and binary formulations. The results indicate that the binary system significantly outperforms individual stabilizers; for example, a formulation containing 10% CKD and 9% CCS achieved a maximum dry density of 1.64 g/cm3, reduced the free swelling rate to 22.7% at 28 days, and reached a UCS of 371.3 kPa. SEM analysis further revealed that the enhanced performance is due to the synergistic formation of hydration products—namely calcium silicate hydrate (C-S-H) and calcium aluminate hydrate (C-A-H)—which effectively fill interparticle voids and reinforce soil structure. These findings demonstrate that the dual mechanism, combining rapid early-stage hydration from CCS with sustained long-term strength development from CKD, offers a cost-effective and environmentally sustainable alternative to traditional stabilizers for expansive soils.